2017
DOI: 10.1021/acs.macromol.6b02766
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing Functional Polymers: Optical Property Recovery of Conjugated Polymer Films by Uncatalyzed Imine Metathesis

Abstract: The implementation of a self-healing functionality into materials has become a prevalent approach for materials which require long-term reliability. As of today, the restoration of mechanical properties has dominated the research on selfhealing materials, whereas research on healing of other functionalities (e.g., conductivity or optical properties) is still in its infancy. Here, the first conjugated polymer, which can restore its optical properties after photodamage is reported. The proposed self-healing mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Furthermore, polymers are often used for coatings, encapsulations or materials with specific optical properties . Transparent materials can get opaque upon damage and lose their applicability for, e.g., solar cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, polymers are often used for coatings, encapsulations or materials with specific optical properties . Transparent materials can get opaque upon damage and lose their applicability for, e.g., solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lei et al demonstrated one way to realize these properties, using a combined imide–imine system which, in addition, is recyclable and self‐healing . Recycling and malleability as well as an improved mechanical strength can also be achieved by carbon fiber composites, as it has been shown by Taynton et al The implementation of imine bonds into conjugated copolymers can be beneficial in order to design highly functional polymers, which can recover their optical properties by healing via the imine metathesis mechanism …”
Section: Healable Polymers Based On Exchange Reactions and Metathesismentioning
confidence: 99%
“…[23] Self-healing can be obtained by generating reversible chemical covalent bonds in the materials network, [24][25][26][27] those chemical interactions include acylhydrazone bonds, [28][29][30] disulfide bonds, [31,32] boronic ester linkages, [33] diarylbibenzofuranone links, [34] thiuram disulfide units, [35] Diels-Alder reactions, [36] and imine bonds (-CH=N-). [37][38][39][40] Notably, Bao and co-workers synthesised a polydimethylsiloxane (PDMS) elastomer with spontaneous self-healing function by forming supramolecular dynamic interactions with coordination complexes. [41] In this work, we propose a synthesis strategy to achieve EM wave absorbing nanocomposites by using dynamic imine bonds-based polyazomethine (PAM) as macromolecular interconnects and Fe3O4-loaded multiwalled carbon nanotubes (Fe3O4@MWCNTs) as EM wave absorbing units.…”
Section: Introductionmentioning
confidence: 99%
“…Impressive progress has been achieved in self-healing mechanical properties of polymers, as for example, reviewed by Yang et al [1] and Ahnere tal. [2] Recently,a lso self-healing concepts to restoree lectronic [3] or optical [4] properties of polymeric bulk materials have been introduced that enablee xtending the lifetime of organic optoelectronic devices. However, the lattere ssentially dependso nt he integrity of the carefully designedi nterfaces between the functional materials, [5] which need to self-heal as well to achieve prolongedl ifetimes of any optoelectronica nd electronic device.…”
Section: Introductionmentioning
confidence: 99%